PERANCANGAN DAN PEMBUATAN ALAT UJI KARAKTERISTIK POMPA SENTRIFUGAL DENGAN SISTEM TUNGGAL, SERI DAN PARALEL - Fiatno, Aris; Ridwan, Abrar (Jurnal Teknik Industri Terintegrasi, 2018)
Design and manufacture of test equipment centrifugal pump characteristics with a single system, serial and parallel so that the pump does not take place in the election that resulted in excess capacity and excess power can be detrimental in operational costs. Operation of the pump with a single system, series and parallel to the head or the necessary capacity can not be achieved with one pump only, it can be used two or more pumps arranged in series or parallel. This created a tool designed for fluid circulating water from a water bath to v-notch with dimensions size, as follows: High P: 100 mm, Height H: 100 mm, Width B: 350 mm, v-notch Length: 1000 mm , Threshold sharp 90 ° through a pvc pipe with a water pump and piping for setting singly, serial and parallel use a regulating valve (valve). Debit (Q) in a single system with a single pump is: 0.00038 m³ / s. Debit (Q) in series with a double pump system is: 0.00049 m³ / s. Debit (Q) in parallel with a double pump system is: 0.00089 m³ / s.